2018
DOI: 10.1101/476291
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variability of soybean response to rhizobia inoculant, Vermicompost, and a legume-specific fertilizer blend in Siaya County of Kenya

Abstract: 2 11 Abstract 12 Rhizobia inoculation can increase soybean yield, but its performance is influenced by soybean 13 genotype, rhizobia strains, environment, and crop management among others. The objective of 14 the study was to assess soybean response to rhizobia inoculation when grown in soils amended 15 with urea or Vermicompost to improve nitrogen levels. Two greenhouse experiments and one 16 field trial at two sites were carried out. The first greenhouse experiment included soils from sixty 17 locations, sam… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 73 publications
1
5
0
1
Order By: Relevance
“…A long root system might have created a greater root-soil contact which increased P uptake hence high P content in shoot and grain. These findings are in agreement with Mathenge [11] who observed that a larger root system enhanced by P provided greater root-soil contact hence higher uptake. Furthermore, high shoot and grain P content can be attributed to the presence of R applied which enhanced the solubilization of the P in the soil increasing available P for the uptake.…”
Section: Conclusion and Recommendationssupporting
confidence: 93%
See 1 more Smart Citation
“…A long root system might have created a greater root-soil contact which increased P uptake hence high P content in shoot and grain. These findings are in agreement with Mathenge [11] who observed that a larger root system enhanced by P provided greater root-soil contact hence higher uptake. Furthermore, high shoot and grain P content can be attributed to the presence of R applied which enhanced the solubilization of the P in the soil increasing available P for the uptake.…”
Section: Conclusion and Recommendationssupporting
confidence: 93%
“…Plant nitrogen concentration in response to increased soil phosphorus supply was observed, with phosphorus content in grain and straw being highest in integration of R and P [10]. Phosphorus and nitrogen play specific roles in symbiotic N2-fixation efficiency through their effects on nodulation and N2-fixation process [11]. High yields with subsequent profits, are related to symbiotic efficiency (SEF) of soybean with N-fixing bacteria [12].…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were reported by Thuita et al [ 98 ] who recommended for sustainable soybean yield increase, to inoculate with Legumefix + sympal (a fertilizer blend for use with rhizobia inoculants) or biofix + sympal to raise yields from 2000 kg/ha to 4000 kg/ha. In poor soils, amendment with vermicompost in addition to Sympal and Legumefix has been shown to improve soybean yields [ 99 ]. Previously, in a study of several commercial rhizobial inoculum, Thuita et al [ 100 ] reported that these products have potential to increase growth, yield, and nitrogen fixation legumes.…”
Section: Bnf and Their Contribution To Agriculturementioning
confidence: 99%
“…Pemberian inokulan bakteri Bradyrhizobium japonicum dapat meningkatkan jumlah bintil akar (Samudin dan Kuswantoro 2018), meningkatkan bobot brangkasan dan bobot akar kering kedelai 44% dan 45% dibanding kontrol (Saadpanah et al 2013). Pembentukan bintil akar dan pertumbuhan dan perkembangbiakan bakteri rhizobium dipengaruhi oleh kultivar kedelai (Reid et al 2011), strain rhizobium (Olivares et al 2013), cekaman abiotik (kemasaman tanah, kekeringan, salinitas) (Lin et al 2012;Rodrigo et al 2017), dan pengelolaan tanaman (Mathenge et al 2019), serta sumber C organik dari pupuk kandang yang mampu membentuk lingkungan kondusif bagi pertumbuhan bakteri (Zengeni et al 2006).…”
Section: Pendahuluanunclassified